2020
DOI: 10.3390/jcm9103175
|View full text |Cite
|
Sign up to set email alerts
|

Falls from Height. Analysis of Predictors of Death in a Single-Center Retrospective Study

Abstract: Falls from height (FFH) represent a distinct form of blunt trauma in urban areas. This study aimed to identify independent predictors of in-hospital mortality after accidental or intentional falls in different age groups. We conducted a retrospective study of all patients consecutively admitted after a fall in eight years, recording mechanism, intentionality, height of fall, age, site, classification of injuries, and outcome. We built multivariate regression models to identify independent predictors of mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The number of intentional jumpers pronounced dead on scene during the COVID-19 period was more than twofold compared to the no-COVID-19 time, even if a significant difference was not observed due to the small number of observations. As already reported by other studies [18,19], after a vertical deceleration trauma, intentional jumpers demonstrated a significantly higher mortality compared to accidental fallers (20.4% vs 5.2%).…”
Section: Discussionsupporting
confidence: 84%
“…The number of intentional jumpers pronounced dead on scene during the COVID-19 period was more than twofold compared to the no-COVID-19 time, even if a significant difference was not observed due to the small number of observations. As already reported by other studies [18,19], after a vertical deceleration trauma, intentional jumpers demonstrated a significantly higher mortality compared to accidental fallers (20.4% vs 5.2%).…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, this is the largest epidemiological Italian study on the topic, providing a complete snapshot of demographics and injury distribution of trauma patients in Italy. The effect of a dedicated trauma system on patients' outcome has already been highlighted in several studies [29,30]. This study demonstrates that the centralization of trauma patients to the level 1 TC has increased considerably over the years, but this trend was not followed by a proportional increase in admission of severely injured patients, defined as ISS ≥ 16, with a consequent marked increase in overtriage.…”
Section: Discussionmentioning
confidence: 56%
“…To our knowledge, this is the largest epidemiological Italian study on the topic, providing a complete snapshot of demographics and injury distribution of trauma patients in Italy. The effect of a dedicated trauma system on patients’ outcome has already been highlighted in several studies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fall from a height is the major accident type [1][2][3]. e spinal and head fractures can lead to severe disability or even death [4][5][6][7][8][9]. e recurrent mistake rate may even increase in people with accident experience.…”
Section: Introductionmentioning
confidence: 99%